SISTEM KONTROL FUZZY LOGIC ALAT PENYIRAMAN OTOMATIS PADA TANAMAN TOMAT DAN KAKTUS: Teknik Elektro - Saputra, Adi; Hasan, Yordan; Alfarizal, Niksen (Teknik Elektro Polsri, 2023)
Plants need proper care, including adequate watering, in order to grow properly and provide optimal results. In an effort to increase the efficiency of watering plants, this study proposes the use of a fuzzy logic control system to control automatic watering devices for tomato and cactus plants. The method used in this study involved collecting relevant environmental data, such as soil moisture, temperature, and light intensity. This data is then processed using the fuzzy logic method to obtain the optimal soil moisture level for each type of plant. The proposed fuzzy logic control system uses several linguistic variables, including